Improving Under-Ring Basketball Shooting through the Use of Bosu Gym Balls and Dumbbell Wrists in Extracurricular Students - Yudhit Wimbinurfalah; Firman Maulana; Muhammad Saleh (Journal Of Sport Education (JOPE), 2025)
The under-ring shoot is a crucial basic basketball skill, but success at ages 12–13 is often hindered by limited arm strength and balance. This two-cycle action research aims to improve the under-ring shoot skills of 12–13-year-old participants in the MTs Al-Ma’tuq basketball extracurricular program through the use of the Bosu Gym Ball (to train stability/balance) and the Dumbbell Wrist (to strengthen arm and wrist muscles). The research procedure included the planning, implementation, observation, and reflection stages. The results showed that the integration of these two tools significantly improved participants’ hand strength, body balance, and shooting accuracy toward the basket. It can be concluded that the use of the Bosu Gym Ball and Dumbbell Wrist is effective in boosting students’ under-ring shoot skills. This study recommends the use of these modified tools as an effective training variation for adolescents.